2014
DOI: 10.14444/1030
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic and lumbar vertebrae morphology in Lenke type 1 female adolescent idiopathic scoliosis patients

Abstract: BackgroundPedicle screws are widely used in adolescent idiopathic scoliosis (AIS) surgeries. Pedicle screw malposition may lead to serious vascular and neurologic complications. Knowledge of the morphometric anatomy of the thoracic and lumbar vertebrae is essential for the surgeon while implanting pedicle screws. It has been reported that there is a reduction of pedicle width at the concavity of the curve in AIS patients. However, it is unclear if gender plays a role in this pedicle width pattern. The goal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…Our study showed clinically relevant smaller pedicle widths (inner and outer cortical) on the concave side periapically-a finding consistent with previous studies using CT, MRI, and cadavers [1,18,21,25,30,35]. Inner and outer cortical pedicle widths were measured to provide clarity over the inconsistencies or ambiguities that existed in the measurement definitions in previous studies [9,36]. With the chord length being longer on the concave side of the curve at T8-T10, but no difference seen in the pedicle lengths, it can be inferred that the length from the anterior cortex of the vertebral body to the anterior aspect of the pedicle along the pedicle axis is longer on the concave side.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our study showed clinically relevant smaller pedicle widths (inner and outer cortical) on the concave side periapically-a finding consistent with previous studies using CT, MRI, and cadavers [1,18,21,25,30,35]. Inner and outer cortical pedicle widths were measured to provide clarity over the inconsistencies or ambiguities that existed in the measurement definitions in previous studies [9,36]. With the chord length being longer on the concave side of the curve at T8-T10, but no difference seen in the pedicle lengths, it can be inferred that the length from the anterior cortex of the vertebral body to the anterior aspect of the pedicle along the pedicle axis is longer on the concave side.…”
Section: Discussionsupporting
confidence: 90%
“…In adolescent idiopathic scoliosis, where the anatomy is three-dimensionally asymmetrically distorted and the pedicles known to at times encroach closer to the spinal cord and aorta [16,32], it is vital to have an understanding of the morphologic features of the pedicle in all planes. While the pedicle width has been investigated in previous studies using various methods [8,9,16,18,30,33,36], there are clear knowledge gaps or inconsistencies when examining the remaining pedicle parameters. The current study identified clinically relevant asymmetry in the width, height, and angulation of the pedicle in multiple planes using a more clinically relevant and reliably reproducible measurement technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is important that spinal surgeons have clear knowledge of the morphometric anatomy of pedicles, especially in deformed spines, to guarantee the safest pedicle screw placement. Using CT scans, we conducted a morphologic study of thoracic pedicles in 60 female patients with Lenke Type 1 adolescent idiopathic scoliosis and 60 sex-, age-, and height-matched controls, which provided a more-accurate assessment than previously published studies because of our large sample size and sample homogeneity [4,12].…”
Section: Discussionmentioning
confidence: 99%
“…5 The accuracy of guidance systems in screw insertion procedures is particularly notable in anatomically difficult cases, such as scoliosis correction surgeries, with a reported 6-fold reduction in perforation rates and mean insertion angle errors compared with conventional methods. 8,14 Similar to other navigation systems, miniature hexapod robots, such as Mazor's SpineAssist or Renaissance, provide intraoperative guidance and physically guide the surgeon along a preplanned trajectory. The Mazor system has been shown to improve surgical accuracy and, in combination with a minimally invasive approach, to minimize morbid sequelae and radiation doses for both patient and clinical staff in several studies.…”
mentioning
confidence: 99%